Rhodium phosphines partnered with the carborane monoanions [CB11H6Y6](-) (Y = H, Br). Synthesis and evaluation as alkene hydrogenation catalysts - Rifat, A; Patmore, N; Mahon, M; Weller, A (2002)
The synthesis of rhodium phosphine complexes partnered with carborane monoanions was reported. These complexes were evaluated as alkene hydrogenation catalysts. It was demonstrated that changing the counterion within the domain of closo-monocarboranes can have a significant effect on the efficiency of hydrogenation by cationic rhodium phosphine catalysts.